Allometry rather than abiotic drivers explains biomass allocation among leaves, stems and roots of Artemisia across a large environmental gradient in China. (5th November 2020) - Liu, Rong; Yang, Xuejun; Gao, Ruiru; Hou, Xinyu; Huo, Liping; Huang, Zhenying; Cornelissen, Johannes H. C.
Abstract: Biomass allocation patterns reflect the adaptive strategies of plants growing in different environments, which is a central issue in comparative plant ecology and evolution. However, the factors underpinning specific allocation patterns across organs and the existence of general rules governing allocation remain contentious. Optimal partitioning theory (OPT) states that plants can respond to resource availability by allocating relatively more biomass to the organ that captures the most limiting resources to optimize growth. In contrast, allometric partitioning theory (APT) postulates that biomass allocation among organs is a power function of plant size independently of environmental variation. As phylogenetic and growth form constraints (e.g. formation of inert heartwood in tree clades) may also affect biomass allocation, comparison among and within closely related taxa of rather similar growth form may enable a more direct testing of which of these two theories prevails. To test whether OPT or APT was prevalent at wide geographical scale, we investigated biomass allocation patterns among leaves, stems and roots of 1, 022 plants of 62 Artemisia species (Asteraceae) collected along broad climate (annual mean temperature range: −4.9 to 18.0°C, annual mean precipitation range: 193–1, 668 mm) and soil gradients (soil carbon content range: 1.6–15.4 kg C m −2 ) in central and eastern China. There were strong allometric relationships among leaf mass ( M L ), stem mass ( M S ) and root mass ( M R ) at both interspecific and intraspecific levels. Moreover, the interspecific and intraspecific patterns were not different from general patterns for pooled plants, that is, M L / M R and M L / M S, but not M S / M R, generally decreased with plant size. However, the three organ mass ratios were not responsive to broad climatic or soil gradients after the effect of plant size was removed. Synthesis . Our results generally support APT instead of OPT, suggesting that Artemisia plants have evolved an allometric strategy rather than relying on adjustment of allocation among organs to adapt to the broadly varying environments at the regional scale. For follow‐up research, we hypothesize that the strong allometric constraints on biomass allocation should depend on strong physiological adaptive responses of the different organs of Artemisia to environmental gradients. Abstract : We determined biomass allocation patterns of Artemisia along large natural environmental gradients in China. Our results generally support APT (allometric partitioning theory) instead of OPT (optimal partitioning theory), suggesting adherence to a rather fixed allometric strategy for this widely distributed genus to adapt to the broadly varying environments. 摘要: 生物量分配模式反映了植物在不同环境中的适应策略，是植物生态学和进化学研究的核心问题。然而，目前对影响器官之间生物量分配模式的主要因子、以及是否存在控制分配的一般规律仍有争议。最优分配理论（OPT）认为，植物优先将生物量分配给可以获取更多限制性资源的器官以促进生长，因此生物量分配模式会对资源可利用性做出响应。相反，异速分配理论（APT）认为，生物量在各器官间的分配模式是与植株大小有关的幂函数，与环境变化无关。此外，系统发育和生长型的限制（如树木形成心材）也会影响器官间的生物量分配模式。利用生长型相似、亲缘关系相近的物种进行研究，可以更直接的检验两种理论的普适性。 为了验证在大的地理尺度上生物量分配模式更符合OPT还是APT。我们在中国中部和东部采集了62种蒿属植物（共1022株），研究区域包含了明显的气候（年均温：‐4.9–18.0℃；年降水：193‐1668mm）和土壤（土壤碳含量：1.6– 15.4 kg C m −2 ）梯度。我们研究了叶、茎和根之间的生物量分配模式。 在种内和种间水平上，叶生物量（ M L ）、茎生物量（ M S ）和根生物量（ M R ）之间都存在显著的异速生长关系。此外，种内和种间异速生长模式与个体水平上的异速生长模式之间没有差异。除 M S / M R 外， M L / M R 和 M L / M S 均随植株的增大而降低。然而，去除异速关系的影响后，三个器官之间的生物量比率并不响应气候或土壤梯度的变化。 结论：我们的研究结果支持APT而不是OPT，表明在区域尺度上蒿属植物进化出了特有的异速生长策略。在不同的环境中，各器官之间倾向于保持特定的异速生长比例，而不是直接依赖于各器官为响应环境变化而调整生物量分配。对于后续研究，我们假设蒿属植物各器官之间生物量分配模式中所受的强烈异速生长限制是依赖于不同器官对环境梯度的生理适应能力。